Application of sericin-based carbon in adsorbing aleurites fordii chiling oil phospholipid

CN122917857APending Publication Date: 2026-10-16SOUTHWEST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510442348.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

磷脂可分为水化磷脂和非水化磷脂,而水脱胶的缺陷在于无法脱除非水化磷脂,磷脂去除率较低;酶法脱胶的脱除效果好,但缺陷在于酶的价格偏高,相对生产成本高

Benefits of technology

[0025] This invention provides the application of sericin-based carbon in the adsorption of phospholipids from *Vernicia fordii* oil. The invention utilizes sericin-based carbon prepared from a solution containing sericin, which is then carbonized to adsorb phospholipids from *Vernicia fordii* oil. The adsorption effect is good, and the oil contains a high content of the active ingredient polyphenols.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917857A_ABST
    Figure CN122917857A_ABST
Patent Text Reader

Abstract

The application provides application of sericin-based carbon in adsorption of phospholipids in Idesia oil. The sericin-based carbon is prepared by carbonizing gel prepared by using a solution containing sericin, and is used for adsorption of phospholipids in Idesia oil, and has good adsorption effect and high content of active ingredients, i.e. polyphenols, in the oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to sericin-based carbon and relates to new applications of sericin-based carbon, specifically its application in the adsorption of phospholipids from *Vernicia fordii* oil. Background Technology

[0002] Edible oil is a vital strategic resource for the national economy and people's livelihood. Currently, my country faces a significant shortage of edible oil, making it crucial to ensure the country's self-sufficiency rate in this area of ​​strategic importance. Woody edible oils, due to their superior nutritional properties and the fact that they do not compete with farmland or food production, can effectively alleviate the supply-demand imbalance and import pressure of grain and oil, making them an advantageous and promising industry for ensuring my country's grain and oil supply security. *Vernicia fordii*, a plant belonging to the genus *Vernicia* in the family Verniciaceae, is a medium-growth timber and oilseed tree species. *Vernicia fordii* oil is rich in unsaturated fatty acids and has extremely high nutritional value. Fully utilizing *Vernicia fordii* resources is beneficial for meeting the edible oil needs of the Chinese people.

[0003] Crude oil, produced from unprocessed oilseed crops, negatively impacts processing quality, storage stability, and sensory characteristics due to the presence of phospholipids. Vegetable oil refining involves degumming, deacidification, decolorization, and deodorization, with degumming being a crucial step in the refining of *Vernicia fordii* oil. Current degumming processes include hydration degumming, acid degumming, membrane degumming, and enzymatic degumming. Phospholipids can be classified as hydrated and non-hydrated phospholipids. A drawback of water degumming is its inability to remove non-hydrated phospholipids, resulting in a low phospholipid removal rate. Enzymatic degumming offers good removal efficiency, but the high cost of enzymes leads to higher production costs. Furthermore, as natural antioxidants, preserving polyphenols in the oilseeds as much as possible during degumming is essential. Summary of the Invention

[0004] To address the problems in the prior art, this invention provides the application of sericin-based carbon in the adsorption of phospholipids from *Vernicia fordii* oil.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] Application of sericin-based carbon in the adsorption of phospholipids from *Vernicia fordii* oil.

[0007] The aforementioned sericin-based carbon is obtained by first preparing a solution containing sericin into a gel, and then carbonizing it. Preferably, the solution containing sericin contains 6-10% (w / v) sericin.

[0008] The above-mentioned gel preparation method is as follows: prepare a carboxymethyl chitosan solution with a concentration of 0.8-1.5% (w / v) using deionized water, and mix it with an equal volume of sericin solution; adjust the pH to 7-8, and refrigerate overnight in a refrigerator at 3-5℃; then prepare the gel using an electrochemical workstation and a three-electrode system.

[0009] The steps for preparing the gel using the electrochemical workstation and three-electrode system are as follows: The three-electrode system is inserted into a mixture of silk fibroin and carboxymethyl chitosan, and a hydrogel is prepared using the current-time curve method. The three-electrode system consists of a graphite sheet electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum sheet electrode as the counter electrode. The current-time curve method uses a gelation voltage of 2-5V and a gelation time of 3-10 minutes. Further, the generated hydrogel is peeled off from the surface of the graphite sheet electrode and immersed in deionized water to remove residues.

[0010] The above carbonization process is as follows: the gel, after being soaked in deionized water to remove residues, is freeze-dried and then placed in a tube furnace for carbonization, wherein the temperature program is set as follows:

[0011] (1): At room temperature, nitrogen is expelled from the air inside the furnace;

[0012] (2): Raise the temperature from room temperature to 120-180 degrees Celsius and maintain it for 1.5-2.5 hours;

[0013] (3): Raise the temperature steadily to 330-380 degrees Celsius and maintain it for 2.5-3.5 hours;

[0014] (4): Raise the temperature to 850-1050 degrees Celsius and maintain it for 1.5-2.5 hours.

[0015] (5): Turn off the furnace and let the sample cool to room temperature naturally.

[0016] In step (1), the nitrogen flow rate is 100 ml / min.

[0017] In step (2), the heating rate is 10 degrees Celsius / minute; in step (3), the heating rate is 5 degrees Celsius / minute; and in step (4), the heating rate is 2 degrees Celsius / minute.

[0018] The freeze-dried sample was then placed in a tube furnace with the temperature program set as follows:

[0019] (1): At room temperature, nitrogen gas is introduced at a flow rate of 100 ml / min to purge the air from the furnace;

[0020] (2): Increase the temperature from room temperature to 150 degrees Celsius at a rate of 10 degrees Celsius / minute and maintain it for 2 hours;

[0021] (3): Then raise the temperature steadily to 350 degrees Celsius at a rate of 5 degrees Celsius / minute and maintain it for 3 hours;

[0022] (4): Increase the temperature from 350 degrees Celsius to 1050 degrees Celsius at a rate of 2 degrees Celsius / minute and hold for 2 hours;

[0023] (5): Turn off the furnace and let the sample cool to room temperature naturally.

[0024] Beneficial effects:

[0025] This invention provides the application of sericin-based carbon in the adsorption of phospholipids from *Vernicia fordii* oil. The invention utilizes sericin-based carbon prepared from a solution containing sericin, which is then carbonized to adsorb phospholipids from *Vernicia fordii* oil. The adsorption effect is good, and the oil contains a high content of the active ingredient polyphenols. Attached Figure Description

[0026] Figure 1 (a) Aqueous solution of sericin obtained after degumming silkworm cocoons; (b) Three-electrode system for preparing sericin-based hydrogels; (c) Sericin-based hydrogel enriched on the surface of a graphite electrode; (d) Sericin-based hydrogel prepared by rinsing to remove impurities and residues; (e) Hydrogel cut into 16 equal parts; (f) Sample after freeze-drying.

[0027] Figure 2 (a) Fruit of *Vernicia fordii*; *Vernicia fordii* oil before (b) and after degumming (c).

[0028] Figure 3 SEM images of (a) lyophilized sericin-based gel, (b) CS, and (c) CS-N2; (d), (e), and (f) are magnified views of the dashed box regions in (a), (b), and (c), respectively; (g) is a SEM image of CSC; (h) is a magnified view of the dashed box region in (g); (i) is a magnified view of the dashed box region in (h); in (i), solid arrows indicate vesicle-like protrusions with micropores, and hollow arrows indicate microporous regions without protrusions.

[0029] Figure 4 Nitrogen adsorption-desorption isotherms of (a) CSC, (b) CS and (c) CS-N2; pore size distribution of (d) CSC, (e) CS and (f) CS-N2.

[0030] Figure 5 XPS spectra of C1s, O1s and N1s of (ac)SS / CMCS, (df)CS, and (gi)CS-N2.

[0031] Figure 6 The maximum adsorption capacity of CS-N2, CS and CSC for MB and ENR.

[0032] Figure 7 The removal rates of phospholipids and polyphenols in *Vernicia fordii* oil by CSC, CS, and CS-N2.

[0033] Figure 8 The removal rates of phospholipids and polyphenols in *Vernicia fordii* oil by different doses of CS-N2 are shown. Detailed Implementation

[0034] The present invention will now be described in detail through specific embodiments. It should be noted that these embodiments are only for further illustration and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description. All raw materials and reagents used in this invention are commercially available products.

[0035] Example 1

[0036] (1) Preparation of sericin aqueous solution

[0037] Cut 20g of silkworm cocoons into fingernail-sized pieces and immerse them in 500ml of deionized water. Then, stir on a magnetic stirrer for 2 hours to ensure thorough immersion. The cocoon-water mixture was then pressurized at 120℃ for 1 hour and cooled to room temperature. After filtering the solution through gauze, the concentration of sericin in the solution was determined using a dry weighing method. Subsequently, the solution was concentrated in a water bath to obtain an 8% (w / v) sericin solution.

[0038] (2) Gel preparation

[0039] A 1% (w / v) carboxymethyl chitosan solution was prepared using deionized water and mixed with an equal volume of sericin solution. After magnetic stirring for 1 hour, the pH of the solution was adjusted to 7.5, and then refrigerated overnight at 4°C. The gel was prepared using an electrochemical workstation and a three-electrode system. The three-electrode system (graphite sheet electrode as the working electrode, Ag / AgCl electrode as the reference electrode, and platinum sheet electrode as the counter electrode) was inserted into the silk fibroin-carboxymethyl chitosan mixture, and hydrogels were prepared using the amperometric It curve method (gelation voltage 3V, gelation time 5min). The generated hydrogel was gently peeled off from the surface of the graphite sheet electrode and immersed in deionized water for 15min. This immersion step was repeated three times to remove residues. The gel was then cut and freeze-dried for later use. Figure 1 ). Figure 1 (a) Aqueous solution of sericin obtained after degumming silkworm cocoons; (b) Three-electrode system for preparing sericin-based hydrogels; (c) Sericin-based hydrogel enriched on the surface of graphite electrodes; (d) Washing the prepared sericin-based hydrogel to remove impurities and residues; (e) The hydrogel was cut into 16 equal parts; (f) Sample after freeze-drying.

[0040] The freeze-dried sample was then placed in a tube furnace with the temperature program set as follows:

[0041] Step 1: At room temperature, introduce nitrogen gas at a flow rate of 100 ml / min to purge the air from the furnace.

[0042] Step 2: Increase the temperature from room temperature to 150 degrees Celsius at a rate of 10 degrees Celsius per minute and maintain this temperature for 2 hours.

[0043] Step 3: Then raise the temperature steadily to 350 degrees Celsius at a rate of 5 degrees Celsius per minute and maintain it for 3 hours.

[0044] Step 4: Increase the temperature from 350 degrees Celsius to 1050 degrees Celsius at a rate of 2 degrees Celsius per minute and maintain it for 2 hours.

[0045] Step 5: Turn off the furnace and allow the sample to cool naturally to room temperature.

[0046] Three types of sericin-based carbon materials were prepared under different nitrogen flow rates during carbonization. Samples prepared by maintaining a nitrogen flow rate of 100 mL / min until the end of the second step, then stopping the nitrogen flow and continuing the subsequent carbonization process, were named CSC. Samples prepared by stopping the nitrogen flow after the first step and then continuing the carbonization process were named CS. Samples prepared by maintaining a nitrogen flow rate of 100 mL / min until the end of the fourth step were named CS-N2. For all three samples, the first step lasted 15 minutes. After carbonization, each sample was rinsed three times with deionized water at 60°C (30 minutes each time), then freeze-dried and stored in a desiccator for later use.

[0047] Degumming of tung oil

[0048] The fruit of *Vernicia fordii* was purchased from Renhuai City, Guizhou Province, China, and the oil was extracted using a pressing method. 5 ml of *Vernicia fordii* oil was heated to 80°C. Then, 100 μL of deionized water at 80°C and 5 mg of sericin-based carbon were added. The mixture was stirred at 500 rpm for 60 minutes at 80°C to ensure thorough mixing of the oil, hot water, and sericin-based carbon. Afterward, the mixture was centrifuged at 4200 rpm for 15 minutes, and the supernatant degummed oil was collected. Figure 2 As shown, there was no significant difference in the appearance of the tung oil before and after degumming. This may be because the degumming process mainly removes impurities such as phospholipids from the oilseed, and has little effect on the color and transparency of the oil. Figure 2 (a) Fruit of the Chinese privet; Chinese privet oil before (b) and after (c) degumming.

[0049] Determination of phospholipid content in tung oil

[0050] The phospholipid content in *Vernicia fordii* oil was determined using inductively coupled plasma optical emission spectrometry (ICP-OES). First, 0.4 g of sample was weighed and transferred to a digestion vessel. Next, 3 mL of concentrated nitric acid and 1 mL of hydrogen peroxide were added. The mixture was then digested on a hot plate at 180 °C for 30 minutes until completely dissolved. After cooling, the digest was evaporated to remove excess acid, and the residue was reconstituted to a final volume of 1 mL. This solution was then transferred to a volumetric flask and diluted to 50 mL with deionized water. The phosphorus content was quantified using a Thermo ICP-OES 7200 spectrometer (Thermo Fisher, USA) according to standard operating procedures (ISO 10540-3:2002).

[0051] Determination of total polyphenol content in tung oil

[0052] The total polyphenol content in *Vernicia fordii* oil was determined according to Chinese National Standard GB / T 8313-2018. Specifically, 1 mL of degummed *Vernicia fordii* oil was placed in a 5 mL centrifuge tube, and then 1 mL of anhydrous ethanol was added. The mixture was vortexed for 10 seconds using a VORTEX-5 vortex mixer (Haimen Qilinbei Instrument Manufacturing Co., Ltd., China) to ensure thorough mixing. The tube was then heated in a 50°C water bath for 30 minutes, vortexing once every 10 minutes. After heating, the mixture was allowed to stand at room temperature until separation. Subsequently, 0.5 mL of the supernatant was transferred to a new 5 mL centrifuge tube, and 2.5 mL of 0.1 mol / L Folin-Ciocalteu reagent was immediately added. After the reaction had proceeded for 8 minutes, 2 mL of 7.5% sodium carbonate solution (w / v) was added. The mixture was homogenized by vortexing and allowed to stand for 60 minutes. Finally, the solution of aliquots was diluted 10-fold with distilled water, and the absorbance was measured at 765 nm using a UV-Vis spectrophotometer.

[0053] Results and Discussion

[0054] like Figure 3 As shown, CSC and CS have morphologies very similar to hydrangeas, exhibiting high specific surface area and hierarchical structure. Under high magnification, vesicle-like protrusions are visible on the surface of CSC, and further magnification reveals microporous structures on these protrusions. Furthermore, dispersed pores are present even in areas without protrusions, significantly increasing the specific surface area of ​​CSC.

[0055] In contrast, the magnified surface morphology of CS and CS-N2 differs significantly from that of CSC. The CS surface lacks obvious protrusions but exhibits a relatively uniform pore distribution. On the other hand, the CS-N2 surface has obvious depressions, but no pore structure was observed. Figure 3 ).

[0056] The inventors hypothesize that these morphological changes are closely related to the generation of volatile byproducts during carbonization and their subsequent secondary reactions with the carbon skeleton. Initially, the release of volatile byproducts may lead to the formation of surface depressions. If these byproducts undergo secondary reactions with the carbon skeleton, they induce the formation of surface bulges and porous structures. After the reaction is complete, the bulges recede, leaving only pores.

[0057] For CS-N2, a continuous nitrogen flow rapidly removes volatile byproducts, preventing further interaction with the carbon skeleton. Therefore, the CS-N2 surface only exhibits depressions, without pore formation. Conversely, in the absence of a nitrogen flow, as in CS, volatile byproducts remain on the carbon skeleton and undergo complete reaction, resulting in a surface rich in micropores but lacking protrusions. CSC represents an intermediate case: in the initial stages of carbonization, from room temperature to 150°C, a nitrogen flow removes volatile byproducts, limiting secondary reactions. Once the carbonization temperature rises above 150°C and the nitrogen flow is stopped, secondary reactions resume. This two-phase process explains the coexistence of microporous vesicle-like protrusions and non-protruding microporous regions on the CSC surface. Figure 3 (a) SEM images of lyophilized sericin-based gel, (b) CS, and (c) CS-N2; (d), (e), and (f) are magnified views of the dashed box areas in (a), (b), and (c), respectively; (g) is the SEM image of CSC; (h) is a magnified view of the dashed box area in (g); (i) is a magnified view of the dashed box area in (h); in (i), solid arrows indicate vesicle-like protrusions with micropores, and hollow arrows indicate micropore areas without protrusions.

[0058] like Figure 4 As shown in Table 1, the nitrogen adsorption-desorption isotherm of CSC is similar to that of CS, both exhibiting a distinct H4-type hysteresis loop, indicating the simultaneous presence of microporous and mesoporous structures in the material. Furthermore, as shown in Table 1, the BET specific surface area, pore area, and pore volume of CSC are all between those of CS and CS-N2. The pore size distribution curves further reveal that the pore size of CSC is mainly concentrated in the microporous region below 2 nm, similar to CS but different from CS-N2. These results clearly demonstrate that the nitrogen flow conditions during carbonization have a significant regulatory effect on the microstructure development of sericin-based carbon. Figure 4 (a) Nitrogen adsorption-desorption isotherms of CSC, (b) CS and (c) CS-N2; (d) Pore size distribution of CSC, (e) CS and (f) CS-N2.

[0059] Table 1. Pore structure characteristics of CSC, CS, and CS-N2 obtained by N2 adsorption isotherm measurements

[0060]

[0061] Specific surface area (S)BET The surface area of ​​micropores (S) was determined using the BET method. mic ), total pore volume (V total ) and micropore volume (V mic )Calculated using the t-plot method.

[0062] Organic elemental analysis (Table 2) showed that CSC had the highest H / C ratio among the three samples. Since the H / C ratio is a key indicator of the aromaticity of a material, this indicates that CSC had the lowest aromaticity among these samples. Furthermore, compared to CS, both CSC and CS-N2 had lower (N+O) / C and O / C ratios, indicating reduced polarity. This may be attributed to the nitrogen flow during the carbonization process promoting the removal of oxygen- and nitrogen-containing volatile byproducts.

[0063] Table 2. Organic elemental analysis results of CSC, CS-N2 and CS

[0064]

[0065] Peak analysis of XPS spectra indicates that ( Figure 5 CSC exhibits a similar functional group composition to CS and CS-N2, with most functional group percentages falling between those of CS and CS-N2 (Table 3). This result suggests that nitrogen flow during carbonization plays a moderating role in determining the functional group composition of the sericin-based carbon surface, potentially influencing its adsorption performance and other physicochemical properties. Furthermore, compared to CS and CS-N2, CSC shows a significantly lower C=C content, indicating that the carbonization conditions for CSC are unfavorable for C=C structure formation. This decrease in C=C content is consistent with the results of elemental organic analysis, which confirms that CSC possesses the lowest aromaticity among these samples.

[0066] Table 3. Chemical composition and corresponding chemical states of CSC, CS-N2 and CS

[0067]

[0068]

[0069] Figure 5 XPS spectra of C1s, O1s and N1s of (ac)SS / CMCS, (df)CS, and (gi)CS-N2.

[0070] Figure 6 This indicates that the adsorption performance of CSC for MB and ENR is between that of CS-N2 and CS, further confirming that the nitrogen flow during carbonization can regulate the secondary reaction between volatile byproducts and the carbon skeleton, and adjust the adsorption performance of sericin-based carbon. Figure 6The maximum adsorption capacity of CS-N2, CS and CSC for MB and ENR.

[0071] Figure 7 The results showed that CSC, CS, and CS-N2 exhibited significant adsorption capacity for phospholipids in *Vernicia fordii* oil, while their adsorption capacity for polyphenols was relatively weak, thus favoring the retention of polyphenols. Among these samples, CS-N2 and CS showed the highest removal rates for both phospholipids and polyphenols, but no statistically significant difference was observed between the two.

[0072] The adsorption performance can likely be attributed to π–π interactions. Specifically, the high C=C content in the unsaturated fatty acids of phospholipids and the aromatic rings in polyphenols can generate favorable interactions with the C=C groups present in the sericin-based carbon. However, CSC contains a significantly lower proportion of C=C groups (as shown in Table 3), which is detrimental to the adsorption of both phospholipids and polyphenols. Furthermore, although CS has the largest specific surface area, its pore size distribution is mainly below 2 nm, which is less effective for adsorbing relatively large phospholipid and polyphenol molecules. This may explain why, despite CS having a larger surface area, CS-N2 and CS show no significant difference in the adsorption performance of phospholipids and polyphenols. Figure 7 Removal rates of phospholipids and polyphenols by CSC, CS, and CS-N2.

[0073] Example 2

[0074] Increasing the CS-N2 dose to 10 mg under the same degumming conditions resulted in an increase in the removal rate of phospholipids to 73.6 ± 7.5%, but this was accompanied by an increase in the removal rate of polyphenols. Figure 8 Removal rates of phospholipids and polyphenols by different doses of CS-N2.

Claims

1. Application of sericin-based carbon in the adsorption of phospholipids from *Vernicia fordii* oil.

2. The application as described in claim 1, characterized in that: Sericin-based carbon is obtained by first preparing a solution containing sericin into a gel, and then carbonizing it.

3. The application as described in claim 2, characterized in that: The solution containing sericin contains 6-10% (w / v) sericin.

4. The application as described in claim 2 or 3, characterized in that, The gel is prepared as follows: a carboxymethyl chitosan solution with a concentration of 0.8-1.5% (w / v) is prepared using deionized water and mixed with an equal volume of sericin solution; the pH is adjusted to 7-8 and the mixture is refrigerated overnight at 3-5 ℃; then the gel is prepared using an electrochemical workstation and a three-electrode system.

5. The application as described in claim 4, characterized in that: The steps for preparing the gel using the electrochemical workstation and three-electrode system are as follows: the three-electrode system is inserted into a mixture of silk fibroin and carboxymethyl chitosan, and the hydrogel is prepared using the current-time curve method; the three-electrode system consists of a graphite sheet electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum sheet electrode as the counter electrode.

6. The application as described in claim 5, characterized in that: The current-time curve method uses a gelation voltage of 2-5 V and a gelation time of 3-10 min.

7. The application as described in claim 1, characterized in that: The generated hydrogel was peeled off from the surface of the graphite sheet electrode and immersed in deionized water to remove residues.

8. The application as described in any one of claims 2-7, characterized in that, The carbonization process involves lyophilizing the gel after soaking it in deionized water to remove residues, then placing it in a tube furnace for carbonization. The temperature program is set as follows: (1): Nitrogen gas is expelled from the air inside the furnace at room temperature; (2): Raise the temperature from room temperature to 120-180 degrees Celsius and maintain it for 1.5-2.5 hours; (3): Raise the temperature steadily to 330-380 degrees Celsius and maintain it for 2.5-3.5 hours; (4): Raise the temperature to 850℃-1050℃ and maintain it for 1.5-2.5 hours; (5): Turn off the furnace and let the sample cool naturally to room temperature.

9. The application as described in claim 8, characterized in that: In step (1), the nitrogen flow rate is 100 ml / min; The heating rate in step (2) is 10 degrees Celsius / minute, the heating rate in step (3) is 5 degrees Celsius / minute, and the heating rate in step (4) is 2 degrees Celsius / minute.

10. The application as described in claim 9, characterized in that: The freeze-dried sample was then placed in a tube furnace with the temperature program set as follows: (1): At room temperature, nitrogen gas is introduced at a flow rate of 100 ml / min to purge the air from the furnace; (2): Increase the temperature from room temperature to 150 degrees Celsius at a rate of 10 degrees Celsius / minute and maintain it for 2 hours; (3): Then raise the temperature steadily to 350 degrees Celsius at a rate of 5 degrees Celsius / minute and maintain it for 3 hours; (4): Increase the temperature from 350 degrees Celsius to 1050 degrees Celsius at a rate of 2 degrees Celsius / minute and maintain it for 2 hours; (5): Turn off the furnace and let the sample cool naturally to room temperature.